2021
DOI: 10.1002/etc.4958
|View full text |Cite|
|
Sign up to set email alerts
|

Short‐Term Aging of Pod‐Derived Biochar Reduces Soil Cadmium Mobility and Ameliorates Cadmium Toxicity to Soil Enzymes and Tomato

Abstract: Contamination of agricultural soil with cadmium (Cd) has become a global concern because of its adverse effects on ecohealth and food safety. Soil amendment with biochar has become one of the phytotechnologies to reduce soil metal phyto-availability and its potential risks along the food chain. Biochar, derived from cocoa pod, was evaluated in soil Cd fractions (exchangeable, reducible, oxidizable, and residual) by modified Commission of the European Communities Bureau of Reference sequential extraction and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…On the one hand, it may be due to the combination of heavy metals and the active protein gene of the enzyme, reducing the binding site of the enzyme, thereby inhibiting the synthesis of the enzyme. On the other hand may be heavy metals make protein deformation, thereby reducing enzyme activity, inhibition of enzyme synthesis [53]. (2) The content of MBC in uncontaminated sugarcane soil was higher than that in manganese-contaminated sugarcane soil, indicating that the activity of microorganisms changed more when biochar was applied to uncontaminated sugarcane soil.…”
Section: Effects Of Biochar Application On Soil Enzyme Activitiesmentioning
confidence: 99%
“…On the one hand, it may be due to the combination of heavy metals and the active protein gene of the enzyme, reducing the binding site of the enzyme, thereby inhibiting the synthesis of the enzyme. On the other hand may be heavy metals make protein deformation, thereby reducing enzyme activity, inhibition of enzyme synthesis [53]. (2) The content of MBC in uncontaminated sugarcane soil was higher than that in manganese-contaminated sugarcane soil, indicating that the activity of microorganisms changed more when biochar was applied to uncontaminated sugarcane soil.…”
Section: Effects Of Biochar Application On Soil Enzyme Activitiesmentioning
confidence: 99%
“…Heavy metals can directly affect soil enzymes and change their activity and diversity. A large number of studies have confirmed that heavy metals are harmful to soil enzyme activities [2,[24][25][26]. Soil enzymatic activities represent the degree to which the terrestrial ecosystems are affected by heavy metals [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The method was successfully able to distinguish seven common polymers collected from the sea and shoreline of the Greek island of Samos in the Aegean Sea. Ogunkunle et al (2020) report the results of a pot experiment to demonstrate the effectiveness of cocoa-pod derived biochar to reduce the mobility of Cd in contaminated soils, enhance soil enzyme activity, and reduce Cd uptake by tomato plants. Agricultural soils become contaminated with Cd from several sources, including as an impurity in fertilisers.…”
mentioning
confidence: 99%